Gender wage gap in Peru and its treatment: reflections about the Equal Pay Law and its Regulation - Salas Zuñiga, Gabriela (2019)
The aim of this article is to analyze gender wage gap in Peru and the suitability of the measures taken by the Peruvian Government to deal with this very complex issue. In order to do so, the author analyzes the definition of the gender wage gap statistical indicator, and the current state of the gender wage gap in Peru, as well as its causes. After that, the author evaluates Equal Pay Law and its Regulation under the lens of international law just to conclude that Equal pay related legislation is consistent with the obligation of the Peruvian Government to adopt measures to overcome de facto inequality situation arisen between men and women in the workplace. Finally, the author identifies the challenges arisen by Equal pay legislation, which, even though could be considered a good first step to eliminate gender wage gap, shall be complemented by additional measures aimed to question gender roles and stereotypes.